Kritik Pemerintah Pada Lagu “Gugatan Rakyat Semesta” Karya Feast; Analisis Wacana Kritis Norman Fairclough - Frima, Mohammad Syafa; Mayasari, Mayasari; Lubis, Fardiah Oktariani (Jurnal Intervensi Sosial dan Pembangunan, 2024)
This research aims to examine the meaning of a song as a tool for criticism, focusing on "Gugatan Rakyat Semesta," which encourages critique of the government. Using a descriptive qualitative method and Norman Fairclough’s critical discourse analysis, the study employs three dimensions of analysis: textual, discursive, and sociocultural. Textually, the song's linguistic elements such as sentence structure, cohesion, coherence, and key terms are analyzed to explore how language functions not only as communication but also as a tool to challenge power and ideology. The discursive dimension investigates the song’s production process by Feast and its reception by the public, particularly during the nationwide student protests in Indonesia in 2022. The sociocultural analysis looks at the broader social conditions surrounding the song, including political events and policies that negatively impacted society. The findings reveal: (1) Textually, the song calls for societal uprising against a corrupt and damaging government; (2) Discursively, the song’s production and release were closely tied to the 2022 protests, with public reception reflecting this context; (3) Socioculturally, the song reflects a broader dissatisfaction with harmful governmental policies. This study contributes to the understanding of how music, particularly protest songs, can serve as a powerful instrument of social and political critique.Keywords Criticism, Government, Song, Critical Discourse Analysis, Norman Fairclough